Zakat Management to Improve the Religious Understanding of The Poor in Baznas: Educational Perspective Islam - Sewang, Ahmad M; Tahir, Muhyiddin; Esse, Indo (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
This article aims to describe Zakat Management in an Effort to Improve the Understanding of the Dhuafa (Islamic Education Perspective) with the problems (1) Zakat management according to the Islamic education perspective (2) Understanding of religion for the dhuafa (3) Efforts to manage zakat to improve the understanding of religion for the dhuafa. This type of research is qualitative research with the research location of BAZNAS Wajo Regency, the approach used is an educational and sociological approach. Data collection methods are interviews, observations and documentation. The research instruments are interview guidelines, observation guidelines, and documentation guidelines. After the data is collected, it is analyzed in three stages, namely data reduction, data presentation and data verification or drawing conclusions and testing data exhaustion. The results of the study found that (1) Zakat management according to the perspective of Islamic education is through 3 stages, namely: collecting zakat through the Zakat Collection Unit (UPZ) in each Village and Sub-district in 14 Districts in Wajo Regency, then distributing zakat covering the fields of economy, education, humanity, health, preaching and advocacy. And zakat supervision is carried out through internal and external audits. (2) The National Zakat Agency (BAZNAS) of Wajo Regency in understanding religion for the dhuafa in economic welfare. Before distributing zakat, the National Zakat Agency (BAZNAS) Baznas holds a meeting with mustahik and provides religious understanding first to the dhuafa. (3) Efforts to manage zakat to improve religious understanding among the poor, namely regulations, policies, work programs of the National Zakat Collection Agency (BAZNAS) of Wajo Regency provide assistance through the Wajo Sejahtera program, providing business capital to sellers of basic necessities, food, drinks, and for motorbike service businesses (workshops), by making agreements to further improve their obedience and carry out their obligations as Muslims.